Determination of fecal carriage rate of Fluoroquinolone Resistant E. coli in Hospital and community Settings of Damaturu, Yobe State, Nigeria - Adam Mustapha; Harun Y Ismail; Baba Zanna Sheriff; Mustafa A Isa; Ibrahim Y Ngoshe (UMYU Journal of Microbiology Research, 2025)
Study’s Excerpt: